Keselamatan Wisatawan Dalam Atraksi Cliff Jumping Yang Terdapat Di Pantai Tegal Wangi Jimbaran Sebagai Daya Tarik Wisata Alternatif - Kurniawan, I Putu Yudi; Ariwangsa, I Made Bayu (JURNAL DESTINASI PARIWISATA; Vol 6 No 2 (2018): VOL 6, NO 2 (2018): (JULY - DECEMBER) JURNAL DESTINASI PARIWISATA, 2019)
The research is concerning safety standardization of Cliff Jumping attraction in Tegal Wangi Beach is motivated by the local and foreign tourist that not knowing yet about potential and safety standardization of Cliff Jumping attraction on Tegal Wangi Beach. Along with the number of tourist visiting which continue to increase resulting local and foreign tourist need to learning about potential and safety standardization of Cliff Jumping attraction on Tegal Wangi Beach. The aim of this research is to knowing about potential and standardization of Cliff Jumping attraction to increase tourist attraction of Tegal Wangi Beach. Data sampling was performed by observation, depth interview, documentation and literature study. The data was obtained with descriptive qualitative analysis. The result of the search shows that safety standardization of Cliff Jumping attraction can be seen in standardization and particular knowing of safety first. Community effort in increasing of Cliff jumping attraction including the effort already being done and the effort that will be done as well as the obstacles faced by the community of Jimbaran Village in increasing of potential Cliff Jumping attraction on Tegal Wangi Beach.   Keyword   :    Safety standardization, Tourist attraction, Alternative tourism